2019
DOI: 10.1371/journal.pone.0218747
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative genetic parameters for growth and wood properties in Eucalyptus “urograndis” hybrid using near-infrared phenotyping and genome-wide SNP-based relationships

Abstract: A thorough understanding of the heritability, genetic correlations and additive and non-additive variance components of tree growth and wood properties is a requisite for effective tree breeding. This knowledge is essential to maximize genetic gain, that is, the amount of increase in trait performance achieved annually through directional selection. Understanding the genetic attributes of traits targeted by breeding is also important to sustain decade-long genetic progress, that is, the progress made by increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 69 publications
(105 reference statements)
6
23
1
2
Order By: Relevance
“…Comparing AC with eucalypts, comparable values in lignin and cellulose contents were found for urograndis hybrids at similar age [38,40], and kraft pulp yield in the same ranges was reported for E. globulus [14,[38][39][40] at ages ranging from 10-16 years and higher wood density. Regarding the S/G ratio, the low mean with a narrow range (1.5-1.8) found for AC in our study is somewhat different from typical S/G ranges reported for eucalyptus species and hybrids [40][41][42].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Comparing AC with eucalypts, comparable values in lignin and cellulose contents were found for urograndis hybrids at similar age [38,40], and kraft pulp yield in the same ranges was reported for E. globulus [14,[38][39][40] at ages ranging from 10-16 years and higher wood density. Regarding the S/G ratio, the low mean with a narrow range (1.5-1.8) found for AC in our study is somewhat different from typical S/G ranges reported for eucalyptus species and hybrids [40][41][42].…”
Section: Discussioncontrasting
confidence: 99%
“…The phenotypic correlations among wood quality traits found in this study are, in general, similar to results reported for other woody species [38,39,42,47]. Kraft pulp yield was correlated with alpha cellulose, glucose, and galactose, and negatively correlated with insoluble lignin.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this study, diameter at breast height (DBH) was the only attribute representing tree growth. Studies across other forest tree species found strong/moderate correlations between DBH and tree height or volume [36][37][38][39] which provides evidence of using DBH as an ideal proxy phenotype for other essential attributes. However, there is decent genetic variability found in DBH -tree height relationship due to differences in individual's response to environment and competition [40].…”
Section: Genetic Backgroundmentioning
confidence: 99%